2019
DOI: 10.47721/arjee20190201018
|View full text |Cite
|
Sign up to set email alerts
|

Climate Variation Assessment Based on Rainfall and Temperature in Ilorin Kwara State Nigeria

Abstract: In recent times and across the globe, the concept of climate has gained much relevance because of its dynamic and complex nature and the significant influence it has on various aspects of the environment, including the increasing threat of global climate change. This study focuses on the assessment of climatic variation in Ilorin based on the variations in rainfall and temperature within the period 1980-2015. Time Series Analysis was used to determine the trend of rainfall and temperature within the period 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The results of the Mann-Kendall test are consistent with previous studies that have reported an increasing trend in temperature in Nigeria. The decreasing trend in rainfall in July in Kwara State (Table 2) is consistent with a study by Olubanjo (2019) which reported a significant decreasing trend in rainfall in the region. However, the increasing trend in rainfall in October is not consistent with the reported decreasing trend in rainfall in Nigeria, suggesting that more research is needed to understand the regional variations in rainfall trends.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the Mann-Kendall test are consistent with previous studies that have reported an increasing trend in temperature in Nigeria. The decreasing trend in rainfall in July in Kwara State (Table 2) is consistent with a study by Olubanjo (2019) which reported a significant decreasing trend in rainfall in the region. However, the increasing trend in rainfall in October is not consistent with the reported decreasing trend in rainfall in Nigeria, suggesting that more research is needed to understand the regional variations in rainfall trends.…”
Section: Resultssupporting
confidence: 90%
“…The statistical analysis revealed that there is a decrease in rainfall in Kwara and Nassarawa States. This is consistent with a study by (Olubanjo, 2019) which reported a significant downward trend in rainfall in the region, especially in July which is in the middle of the cropping season. Although more studies are needed in the region to establish the intra-annual rainfall change both men and women surveyed perceived the rainfall differently.…”
Section: Gendered-differentials and Gender-responsive Approaches To A...supporting
confidence: 93%
“…Ilorin is the Kwara State capital city https://doi.org/10.58985/jafsb.2024.v02i01.32 (North-Central Nigeria) located within latitude 8 o 33'N and longitude 4 o 33'E. The city is within the tropical savannah climate (Köppen climate classification) with annual rainfall of 990.3-1,310 mm (39-52 in), maximum temperatures ranging between 33-37 o C (91.4-98.6 o F) with the hottest month being March while the relative humidity (RH) ranges between 29-70.2% from month to month [22].…”
Section: Study Areamentioning
confidence: 99%